2022
DOI: 10.1155/2022/6917009
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal Outcomes and Associated Factors among Mothers with Hypertensive Disorders of Pregnancy in Suhul Hospital, Northwest Tigray, Ethiopia

Abstract: Background. Hypertensive disorder of pregnancy is the leading cause of maternal and perinatal morbidity and mortality worldwide and the second cause of maternal mortality in Ethiopia. The current study is aimed at assessing fetal-maternal outcomes and associated factors among mothers with hypertensive disorders of pregnancy complication at Suhul General Hospital, Northwest Tigray, Ethiopia, 2019. Methods:A hospital-based cross-sectional study was conducted from Oct. 1st, 2019, to Nov. 30, 2019, at Suhul Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
2
5
2
Order By: Relevance
“…This could be attributed partly to the fact that gestational age at termination of pregnancy in our study was earlier than 4 previous studies. It is, however, important to emphasize that the stillbirth rate and perinatal mortality rate in our study were lower than the reports from Ethiopia [ 12 , 15 ], India [ 13 ], and Uganda [ 14 ]. Moreover, the prevalence of adverse maternal outcomes including placental abruption (1.6%), pulmonary edema (0.4%), eclampsia (1.2%), and HELLP syndrome (3.9%) in this study were also lower as compared to 4 previous studies.…”
Section: Discussioncontrasting
confidence: 81%
“…This could be attributed partly to the fact that gestational age at termination of pregnancy in our study was earlier than 4 previous studies. It is, however, important to emphasize that the stillbirth rate and perinatal mortality rate in our study were lower than the reports from Ethiopia [ 12 , 15 ], India [ 13 ], and Uganda [ 14 ]. Moreover, the prevalence of adverse maternal outcomes including placental abruption (1.6%), pulmonary edema (0.4%), eclampsia (1.2%), and HELLP syndrome (3.9%) in this study were also lower as compared to 4 previous studies.…”
Section: Discussioncontrasting
confidence: 81%
“…The study also found that exposed women who did not travel by ambulance were more than twice as likely as nonexposed women to have adverse perinatal outcomes (AOR =2.6, 95% CI: 1.21–5.50). This finding is supported by studies done in different parts of Ethiopia [ 6 , 7 , 28 , 29 ] whereas no similar findings have been found in other countries. Negative perinatal outcomes worsen when labouring women do not arrive at the hospital on time due to traffic congestion.…”
Section: Discussionsupporting
confidence: 53%
“…Any conditions affecting the mother's health during pregnancy, labour and delivery, and postnatal period have a direct impact on the infant's well-being [ 4 , 5 ]. This is due to the close interrelationships of maternal and neonatal health [ 4 , 6 , 7 ]. Failure to improve birth outcomes by 2035 will result in an estimated 116 million deaths, 99 million survivors with disabilities, and 52 million stillbirths [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 10 Women admitted at <34 weeks, age 16–24 years, lower wealth quintiles and rural residence had also a positive association with unfavourable maternal outcomes. 9 Further, gestational age at admission, 18 onset of the disease and low haemoglobin level 19 were predictors of maternal complication.…”
Section: Introductionmentioning
confidence: 92%